Sistem Pendukung Keputusan Pemilihan Mahasiswa Berprestasi Menggunakan Metode TOPSIS - Dendy Frans Gunawan Hutagalung; Mesran Mesran (Bulletin of Artificial Intelligence, 2024)
Public and private universities are institutions where students acquire knowledge according to their interests and talents. To improve student quality, universities implement programs for selecting outstanding students. However, in many public and private universities, the selection of outstanding students is often based solely on the Grade Point Average (GPA). In fact, several other assessment criteria should also be considered, such as the number of scientific papers, TOEFL score, GPA, ethics, and parents’ monthly income. Therefore, a decision support system is required to assist in the selection process of outstanding students. The method applied in this study is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This method is chosen because it can effectively solve decision-making problems by using priority values or weights assigned to each criterion. The results of this study indicate that Alternative A3, namely “Frans,” is the best alternative with a preference value (Vi) of 1